Pemberdayaan Peran Kader Posbindu Dalam Peningkatan Derajat Kesehatan Lansia berbasis Budaya Di Puskesmas Depok - Mira Asmirajanti; Antia Antia; Erwan Baharudin; Gledys Oksecargra; Khairina Arare; Chairuni Shaliha Nurfitra; Evi Medina Oktavia; Ratu Dini Rahmawati (Universitas Majalengka, 2023)
Posbindu activities are promotional and preventive activities that involve the community. The planing, implementation, and monitoring, as well as assessments are carried out from and by the community. Skills of health cadres are required in posbindu activities. Improving the ability of cadres in communication and posbindu services as a forum for services to the elderly needs to be carried out, especially preventive and promotive. The method used in this service is counseling and training of health cadres who are expected to detect risk factors for the elderly with prevention as early as possible. The activity was held on November 10, 2022, attended by 17 cadres posbindu hebras, posbindu gelatik A, and posbindu flamboyan B. The results of the activity are known to have increased cadre knowledge about “warga emas“ elderly, herbal therapy, massage therapy, accupressure, and supplementary feeding of the elderly. Through community service activities, the empowerment of posbindu cadres, especially in communication, can increase motivation and provide information to the elderly community.